2013
DOI: 10.1063/1.4773998
|View full text |Cite
|
Sign up to set email alerts
|

Giant negative uniaxial magnetocrystalline anisotropy of Co80Ir20 sputtered films with perfect hexagonal-close-packed and composition-modulated atomic layer stacking

Abstract: Co80Ir20 films with negative uniaxial magnetocrystalline anisotropy (Ku) are investigated with respect to the regularity of the stacking sequence and atomic site arrangement. Substrate heating at 600 °C enhances the negative Ku of Co80Ir20 to −9.6 × 106 erg/cm3. X-ray diffraction analysis and scanning transmission electron microscopy of the Co80Ir20 film fabricated at 600 °C indicate (1) a near perfect hexagonal-close-packed (hcp) stacking structure and (2) an atomic layered structure that consists of randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Their potential applications in the high-frequency area, such as inductor, noise suppressor, and field generation layer inside a spin torque oscillator, further spur researchers to investigate the moment distribution and property manipulation of soft magnetic thin films. In soft magnetic thin films [14], their moment distribution and macroscopic properties are strongly affected by the domain structure and the domain structure even determines their practical applications [5, 6]. In perpendicular magnetic recording, the existence of the Bloch wall in a soft magnetic underlayer causes the appearance of an out-of-plane stray field [7].…”
Section: Introductionmentioning
confidence: 99%
“…Their potential applications in the high-frequency area, such as inductor, noise suppressor, and field generation layer inside a spin torque oscillator, further spur researchers to investigate the moment distribution and property manipulation of soft magnetic thin films. In soft magnetic thin films [14], their moment distribution and macroscopic properties are strongly affected by the domain structure and the domain structure even determines their practical applications [5, 6]. In perpendicular magnetic recording, the existence of the Bloch wall in a soft magnetic underlayer causes the appearance of an out-of-plane stray field [7].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the HAADF method was found to be quite effective to observe layers sequence and compositional atomic layer stacking structure. 14) The intensity of a HAADF image is generally proportional to the square of the average atomic number of a sample. 18),19) Therefore, the contrast of the HAADF image is mainly caused by the difference in composition.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are many works which indicate that CoIr alloy with hcp structure shows strong negative uniaxial magnetocrystalline anisotropy (K u grain ) with the doping of Ir. [1][2][3][4][5] In this case, the easy magnetization direction is along c-plane or perpendicular to caxis. In the reported literature on CoIr, most of their works focused on the static magnetic properties for potential application of soft underlayer in magnetic recording.…”
Section: Introductionmentioning
confidence: 99%
“…In the reported literature on CoIr, most of their works focused on the static magnetic properties for potential application of soft underlayer in magnetic recording. 1,4,5 With the development of information technology and electromagnetic devices, the application of high-frequency soft magnetic films becomes more and more extensive, such as microwave absorber, micro-inductor, micro-transformer, and magnetic head with high writing speed. [6][7][8][9][10] Recently, CoIr film has a great application prospect for high-frequency application due to its novel high-frequency magnetic properties with negative K u grain .…”
Section: Introductionmentioning
confidence: 99%